Rheological Parameters of Carotid Circulation in Metabolic Syndrome with or without Diabetes Mellitus - Alen Hajdarević; Dragan Piljić; Fahrudin Šabanović; Dilista Piljić; Farisa Babić; Ajdin Beganović; Juš Kšela (Acta Clinica Croatica, 2024)
The aim of this research was to examine the rheological parameters of carotid arteries and the frequency of abnormal values in patients with metabolic syndrome (MetS) with and without diabetes mellitus (DM). The sample consisted of 90 subjects and was divided into two equal groups. The first group consisted of patients with MetS but without DM, while the second group had both MetS and DM. We used the values of the peak systolic velocity (PSV) as a reference for pathology. The results showed pathological values of PSV in the right internal carotid artery (ICA) in twelve patients in the MetS + DM group. The study found that the incidence of pathological rheological parameters was higher in subjects with MetS + DM as compared to those with only MetS. Subjects with MetS + DM had higher values of maximum acceleration during systole in various carotid arteries. A subject with MetS + DM also showed total flow obstruction in the left and internal carotid artery (ICA) and a severe narrowing of the right ICA, indicating the presence of carotid artery disease. The study also found that nearly two-thirds of subjects with MetS + DM had pathological values of PSV in the right ICA and slightly fewer in the left ICA. Research on French populations has shown similar results. Eleven patients had pathological values in the left ICA. The frequency of the carotid rheological parameters’ abnormalities was significantly higher in the MetS with DM patient group. The frequency of abnormalities in the rheological parameters of carotid circulation was significantly higher in patients with MetS and DM (as compared to non-diabetic patients). In our study, pathological changes were generally more susceptible to ICA. This indicates the importance of screening the rheological parameters of subjects with MetS for the prevention and treatment of cerebrovascular disease.